Analisis Hubungan Lingkungan Fisik Rumah Terhadap Kejadian COVID-19 di Lingkungan Perumahan Kelurahan Sragen Kulon - Zahra Imalia; Ririh Yudhastuti; Syifa'ul Lailiyah (Media Gizi Kesmas, 2024)
Background: COVID-19 is one of the infectious diseases. Various interactions between factors can cause infectious diseases, commonly known as the epidemiological triad. The factors in the epidemiological triad include agents, hosts, and the environment. One of the villages in Sragen Sub-district affected by COVID-19 is Sragen Kulon with a population density of 6544.22/km2. Sragen Kulon Urban Village is a densely populated area that is included in the coverage area of the Sragen Health Center. Objective: This study aims to analyze the relationship between the physical environment of the house and the incidence of COVID-19 in the residential housing environment of Sragen Kulon Village, Sragen Regency in 2022. Methods: This research method is observational analytic with cross-sectional study design. This study use a random sampling technique with a sample size of 90 people who resided and settled in the Sragen Kulon area according to predetermined inclusion and exclusion criteria. Primary data collection using questionnaires and observation sheets. Bivariate data analysis using chi square with p<0.05. Results: The results of bivariate analysis using chi square analysis show that physical environmental variables which correlate with the incidence of COVID-19 in Sragen Kulon Village with p<0.05 were residential density (p=0.016), ventilation (p=0.019), and humidity (p=0.003). The variable that has no correlation with the incidence of COVID-19 in Sragen Kulon Village with p>0.05 is temperature (p=0.197). Conclusion: There is a correlation between the physical environment, such as density of occupancy, ventilation, and humidity, and the incidence of COVID-19 disease in the residential housing environment of Sragen Kulon Village.